Primary osteogenic sarcoma of the breast (2006)
Background: Primary extra-osseous osteogenic sarcomas have been reported in many tissues of the body but their occurrence in the breast is extremely rare. It can arise as a result of osseous metaplasia in a pre-existing benign or malignant neoplasm of the breast or as non-phylloides sarcoma from the soft tissue of a previously normal breast. Case presentation: A 40 year-old Nigerian woman was clinically diagnosed to have carcinoma of the left breast. The histology report of core-needle biopsy of the mass showed a malignant neoplasm comprising islands of chondroblastic and osteoblastic stromal cells. This report changed the diagnosis from carcinoma to osteogenic sarcoma of the breast. She had a left modified radical mastectomy, however there was significant post surgery skin deficit. A latissimus dorsi musculocutaneous flap was used to cover the anterior chest wall defect. Sections from the mastectomy specimen confirmed the diagnosis of osteogenic sarcoma. She died six months after mastectomy. Conclusion: A diagnosis of osteogenic sarcoma of the breast was made based on histology report and after excluding an osteogenic sarcoma arising from underlying ribs and sternum. This is the second documented case of primary osteogenic sarcoma of the breast coming from Nigeria